2006
DOI: 10.1007/s00261-006-9034-y
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of 310 patients: can early CT predict the severity of acute pancreatitis?

Abstract: Background: This study was designed to determine the most important early CT parameters predictive of acute pancreatitis severity. Methods: Three hundred and seventy-one consecutive patients with acute abdominal pain and hyperamylasemia were enrolled. Three hundred and ten of the 371 patients met our inclusion criteria. Acute pancreatitis severity was evaluated using the 1992 Atlanta criteria. Different CT parameters were reported from the admission abdominal CT by two radiologists blinded from any clinical pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 27 publications
2
17
0
1
Order By: Relevance
“…An extrapancreatic finding can be assessed on the basis of the CT scan (cholecystolithiasis, choledocholithiasis, vein thrombosis and ascites) or other abnormalities in the abdominal cavity. MRI provides very similar results [14][15][16][17] .…”
Section: Classification Of Acute Pancreatitis With the Use Of Imagingsupporting
confidence: 73%
“…An extrapancreatic finding can be assessed on the basis of the CT scan (cholecystolithiasis, choledocholithiasis, vein thrombosis and ascites) or other abnormalities in the abdominal cavity. MRI provides very similar results [14][15][16][17] .…”
Section: Classification Of Acute Pancreatitis With the Use Of Imagingsupporting
confidence: 73%
“…However, MCTSI was more closely associated with patient outcome than CTSI in our study. Several studies reported a strong correlation between the CT evaluation and the clinical severity of acute pancreatitis [14,20,21] and some studies have not corroborated these findings [22][23][24].…”
Section: Correlation Of Ct Scoring Indexes With Patient Outcome Parammentioning
confidence: 99%
“…a bowel perforation. However, there is no consensus whether to perform a CT in the early course of AP as a prognostic indicator [4,9,11,14,15,16,17,18,19,20,21,22,23]. Scientific proof that development of pancreatic necrosis occurs as early as within 96 h after symptom onset is disputable [15].…”
Section: Introductionmentioning
confidence: 99%